Evaluation of Lontar Prasi Bali Application based on Augmented Reality Using User Experience Questionnaire - I Gede Iwan Sudipa; Putu Wirayudi Aditama; Christina Purnama Yanti (PT FORMOSA CENDEKIA GLOBAL, 2022)
The digitalization era supports the use of technology to preserve and strengthen local culture, such as using Augmented Reality (AR) to visualize Lontar Prasi figures and stories. To design and operate the Lontar Prasi Bali AR application optimally based on user demands, User Experience (UE) testing was conducted on 56 respondents with 8 questions on the application using User Experience Questionnaire (UEQ) test shows that the average pragmatic and hedonic quality is 1.94, meaning the application is good at providing user pleasure and comfort. The Lontar Prasi Bali AR app provides above-average results (Excellent) and matches user expectations.